THE CUTOFF TIME POINT OF THE PARTIAL AREA METHOD FOR ASSESSMENT OF RATE OF ABSORPTION IN BIOEQUIVALENCE STUDIES - Macheras, P.; Symillides, M; Reppas, C (PHARMACEUTICAL RESEARCH, 1994)
The partial area method has been suggested for the assessment of the absorption rate in bioequivalence studies. This paper provides a theoretical basis for the estimation of the optimal cutoff time point of the partial areas for drugs with one compartment model disposition. The analysis is performed by using the appropriate equations which relate the normalized (in terms of the extent of absorption) partial areas with time expressed in terms of multiples of half-life. Provided that the quality of experimental data ensures precise estimation of the parameters, the t(max) of the formulation with the faster absorption characteristics is generally the most practical cutoff time point for calculation of the normalized partial areas, when a drug follows one compartment model disposition with linear absorption.
Keywords: absorption rate; bioequivalence; CUTOFF TIME; PARTIAL AREA METHOD